(E)-4-Methoxy-N′-(2,4,5-trifluorobenzylidene)benzohydrazide monohydrate - R. Maheswari; J. Manjula; B. Gunasekaran; G. Bakiyaraj (IUCrData, 2016)
The title Schiff base compound, C15H11F3N2O2·H2O, crystallized as a monohydrate. The conformation about the C=N bond is E. The molecule is almost planar, with the dihedral angle between the planes of the methoxybenzene and trifluorobenzylidene rings being 7.46 (6)°. In the crystal, molecules are linked by bifurcated Owater—H...(O,N) hydrogen bonds and N—H...Owater and Owater—H...O and C—H...O hydrogen bonds, forming chains along [100]. The chains are linked by C—H...Owater hydrogen bonds, forming slabs parallel to the bc plane. Within the slabs there are offset π–π interactions present [intercentroid distance = 3.7883 (7) Å].